Spontaneous Bone Healing after Cysts Enucleation without Bone Grafting Materials (Journal of Hama University, 2021)
The aim of this study was to evaluate spontaneous bone regeneration after cystsenucleation of the jaws without the use of bone grafting materials. We included 10patients at random (6 men and 4 women) with amean age of 31.8 years, with jaw cysts treated by enucleation, without the use of grafting materials. A method of measurements to assess the percentage of reduction of the bone cavities was used to objectify the results. The patients were evaluated before and at 6 months after surgery, with panoramic radiograph . The analysis of the sample shows an average of 85.59% decrease in horizontal measures, 89.53% in the vertical, and 88.98 and 89.81% in the diagonal left and right, respectively. The total average reduction was 88.47%. It showed a greater decrease in vertical and diagonal measurements with respect to horizontal. Regeneration in 3 patients was 100% and in 7 patients was higher at 50.4%. The results suggest that in some cases, spontaneous bone regeneration can be achieved by cysts enucleation without bone grafting materials